2020
DOI: 10.1177/2324709620905954
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Lobular Breast Cancer Causing Hydronephrosis

Abstract: Breast cancer is the leading malignancy and the second most common cause of mortality in women. Although there have been advances in identifying biomarkers as potential targets for therapy, triple-negative breast cancer (TNBC) continues to have a poorer prognosis than the other receptor subtypes. The most common sites of metastasis are bone, liver, lung, and brain. We present a patient with known TNBC presenting with nausea and vomiting in whom computed tomography revealed a right-side pelvic mass causing hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…An up-to-date literature review has shown that our case is the third one, published on TNBC, presented with invasion of the ureter; one case being a male patient [ 18 , 19 ] ( Table 1 ). ER+/PR−; HER2+, and ER+/PR+; HER2+ breast malignancies have also been reported [ 13 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An up-to-date literature review has shown that our case is the third one, published on TNBC, presented with invasion of the ureter; one case being a male patient [ 18 , 19 ] ( Table 1 ). ER+/PR−; HER2+, and ER+/PR+; HER2+ breast malignancies have also been reported [ 13 ].…”
Section: Discussionmentioning
confidence: 97%
“…A 18 F-FDG PET/CT was performed, and no hypermetabolic lymph nodes were detected either above or below the diaphragm. The already known lesion of the right ureter was not visible on PET due to the small size of the lesion and the presence of radioactive urine at the area of interest.…”
Section: Case Reportmentioning
confidence: 99%
“…A PubMed search for the keywords "breast cancer" and "hydronephrosis" identified 10 cases of postoperative recurrence, as shown in Table 2 [3][4][5][6][7][8][9][10][11][12]. The median time from surgery to diagnosis of hydronephrosis was 76.5 months (18-360 months), and the histological type was IDC in 4 cases, ILC in 5 cases, and unknown in 1 case.…”
Section: Discussionmentioning
confidence: 99%